Effectiveness of giving dragon fruit and ambon banana to increase haemoglobin levels in anaemic adolescent girls - Yati Supriati; Istiana Kusumastuti (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Background: Anemia is a common health problem among adolescent girls, especially in areas with limited access to nutritious food. One of the efforts to overcome anaemia is to increase the consumption of iron-rich fruits, such as dragon fruit and ambon banana. Objective: to evaluate the effectiveness of dragon fruit and ambon banana administration in increasing haemoglobin levels in anaemic adolescent girls Method: Qualitative research combines observational and intervention approaches. The research sample amounted to 2 adolescent female respondents. Instrument of treatment activities using a checklist sheet on elevated haemoglobin levels. Results: An increase in haemoglobin levels was obtained in adolescents given dragon fruit juice, where the first week was 10.1 g / dl, the second week was 11.2 g / dl, and the fourth week was 12.3 g / dl. There was a slightly slower increase in haemoglobin levels in adolescents who were given Ambonese bananas in the first week of 10.2 g / dl, the second week of 10.8 g / dl, and the fourth week of 11.3 g / dl. Conclusion: respondents who consume dragon fruit increase haemoglobin levels faster than bananas. It is expected to be used as alternative midwifery care for the midwife profession by giving dragon fruit juice to increase haemoglobin levels. Teenagers are advised to maintain a balanced diet by consuming fruits rich in iron and nutrients, such as dragon fruit and ambon, bananas and other essential nutrients. By maintaining a balanced diet and increasing the consumption of iron-rich fruits, adolescents can improve their haemoglobin levels and maintain overall body health